PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Altina Damaiyanti; Siti Komariah Hildayanti; Meilin Veronica (Jurnal Manajemen, 2023)
This study aims analyze service quality and price on customer loyalty with customer satisfaction as an intervening variable for Café Victoria consumers. This type of research is descriptive quantitative, sampling in this study used 120 respondents. The results of the study were that there was an influence between service quality on customer satisfaction at Café Victoria Babat Toman with the t test result of 0.000 ˂ 0.05. There is also an effect of price on Café Victoria's customer satisfaction the t test result of 0.000 ˂ 0.05. Service quality also affects the loyalty of Café Victoria Babat Toman consumers, the results of the t test which gives a significance value of 0.009 ˂ 0.05. The test results show that price affects customer loyalty at Café Victoria Babat Toman with a t-test result of 0.000 ˂ 0.05, the test results show that customer satisfaction affects Café Victoria customer loyalty. This is supported by the t-test result of 0.00 <0.05. Simultaneously, there is an influence between service quality and price loyalty through customer satisfaction as an intervening variable on customer loyalty at Café Victoria. This is evidenced by the results of the F test with a significance value of 0.000 ˂ 0.05.